Propuesta de diseño de un sistema de gestión de calidad basado en la norma iso 9001:2015 para su implementación en el área de operaciones para incrementar los beneficios económicos en la Empresa de Transportes n&m Moncada s.r.l. - Velasquez Baca, Yolving Henderson (2020)
The main objective of this research was to determine the impact of the management system based on the ISO 9001: 2015 standard on the economic benefits of the company TRANSPORTES N&M MONCADA S.R.L. The management system that the company managed was diagnosed through a checklist of requirements of ISO 9001: 2015, reaching 32% compliance with the requirements of the aforementioned standard, for this reason the documented information necessary to align the management of the company to the norm in question, also a plan of implementation of the system obtained was elaborated. Thus, after the preparation of the documentation, there was a 53% increase in compliance with the requirements of the standard. Finally, with the economic evaluation of the proposal for this project, a NPV of S /18 ,024.49 was obtained, an IRR of 28.75% and a cost benefit of 1.4, which concludes that it is feasible for the company TRANSPORTES N&M MONCADA SRL And it is proposed Implement the management system.